As metáforas conceptuais nas homilias do Papa Francisco - Carvalho, Sérgio Ricardo Pereira de (2017)
The present research proposes to analyse the metaphorical concepts of certain terms used constantly in Pope Francis homilias. In that sense, we will try to investigate, through metaphorical linguistic expressions, how the concepts of heart, mistery, faith and charity are categorized in popal homilias in the perspective of the metaphorical MCIs. Therefore, we depart from the hipothesis that, in the homilias given by the Pope, the meaning of the above mentioned concepts relies on religious, ideological and cultural conception which should be followed by the faithful in their christian practice. As theoretical reference, we used the Theory of Metaphorical concept built by Lakoff and Johnson (2002 [1980]), the Cognitive Models idealized by Lakoff (1987) and the contributions of Feltes (2007), the interface studies between metaphor and culture under the perspective of Kovecses (2005) and the relation between metaphor and ideology, introduced by Goatly (2007) and Charteris – Black (2004). The corpus used for this study is made up of 65 homilias extracted from the Holy Site, given from January to December 2015. The qualitative analysis of the data confirmed our hipothesis that the metaphors used reflect the cultural/ ideological values, which should be followed by the religious communitity. We verified that the concept of heart was a metaphorically categorized as recipient, which may be full/empty, open/closed and where people and feelings can enter/leave. The concept of mistery, which in the religious perspective means a plan of God towards salvation, was also categorized as recipient, in which the faithful may be placed considering only the aspects in/out as limits of this recipient. The concept of faith was understood as living being due to inherent character and experiences we have as members of that group. Finally, the concept of charity, is seen as person, through the characters of humane domaine.